Analisis Perbandingan Manajemen Laba dan Audit Delay pada Perusahaan Keluarga dan Perusahaan Non-Keluarga yang Terdaftar di Bursa Efek Indonesia (BEI) Periode Tahun 2023-2025 - Andreas Wreda Adiwardana; Marheaendra Kusuma; Miladiah Kusumaningarti (Jurnal Kendali Akuntansi, 2026)
This study examines differences in earnings management and audit delay between family and non-family firms. It aims to analyze the characteristics of both variables and determine whether significant differences exist between the two groups. A quantitative comparative approach was employed using financial statement data from companies listed on the Indonesia Stock Exchange (IDX) during 2023-2025. Samples were selected based on predetermined criteria, and data were collected through documentation. Earnings management was measured using discretionary accruals based on the Modified Jones Model, while audit delay was calculated from the time between the fiscal year-end and the audit report date. The results show that family firms tend to engage in lower earnings management than non-family firms. Family firms also experience longer but more consistent audit delays, whereas non-family firms complete audits more quickly but with greater variation. Statistical tests reveal a significant difference in audit delay but no significant difference in earnings management. These findings indicate that ownership structure affects financial reporting behavior and audit timeliness. The study contributes by comparing family and non-family firms, providing insights into financial reporting quality and corporate governance.